YIELDS AND CHARACTERISTICS OF BINTANGUR OIL FROM ENGGANO ISLAND AS RAW MATERIAL FOR MAKING BIODIESEL - Devi Silsia; Ridwan Yahya (Jurnal Agroindustri, 2019)
The potential and dominance of the Bintangur Tree on Enggano Island is quite large. Bintangur seed  has a high oil content, and is not included in the food category. Bintangur oil is one of the vegetable oils that has the potential as a biodiesel feedstock. This study aims to determine the yield of Bintangur seed oil and the characteristics of crude oil produced. Bintangur seeds are obtained from the villages of Banjar Sari, Kaana and Apoho Enggano. Bintangur oil was extracted with n-hexane solution using soxlet. The oil characteristics observed included water content, density and free fatty acid content (FFA). The extraction results in the form of yellow oil with the yield of oil obtained ranged from 48.07 - 73.71%. Characteristics of crude oil produced has water content of 1.2 - 2%, density 0.910 - 0.920 and FFA 15.51 - 17.97%